Pengharapan dalam Terang Ajaran Iman Katolik - Situmorang, Markus (Forum, 2023)
In the Catholic faith, hope is specifically defined as theological virtue. Hope is not just a psychological impulse or temporary emotion but the fruit of faith in Jesus. The finality of hope does not stop at earthly things. However, this does not mean that we should not hope for good things while in this world. The purpose of this study is to answer the difficulties of Christians in understanding and living the meaning of hope in the midst of a world full of challenges. The method used in this research is a qualitative method using literature study. Scripture texts, Church documents and the thoughts of theologians that discuss hope will be studied using descriptive analysis. The results of this study show that in facing of bitter and dark experiences in life, the followers of Christ must remain steadfast in hope. The correct understanding of hope makes believers strong in facing challenges and problems. A follower of Christ needs to direct every hope to heaven as the finality of life on earth.